MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA PERBANKAN - Salfutra, Reko Dwi (Fakultas Hukum Universitas Bangka Belitung, 2017)
The more banks offer a number of products to the public, the possibility of a dispute between banks and customers is increasingly wide open as well. The existence of the customer service department in the bank is more than just a small talk. In the execution of its daily duties, in the banking world there are also frequent disputes between banks and their customers. In fact, not infrequently the dispute settlement that is used to bring the disputing parties to the world of justice that seem convoluted and long-winded. Therefore, any banking dispute requires fast and precise settlement efforts, and is empowered to achieve mutual interests.